Digital Competences of Teachers in the Higher Education Academic Development System: Experience of the Empirical Research - A. V. Noskova; D. V. Goloukhova; E. I. Kuzmina; D. V. Galitskaya (Высшее образование в России)
The article analyzes the problem of higher education teachers’ digital competence formation in relation to the university academic development. In the system of academic development, a higher education teacher becomes an active subject and an object of influence of the university structures.The notion of “academic capital” – a system of professional competencies of a teacher, in whose structure digital competencies acquire special importance, is introduced to assess the effectiveness of academic development.It is assumed that depending on the attitudes towards the development and integration of digital competencies into professional practices, teachers are divided into different categories according to their role in the academic development.In order to test the hypothesis, focus group research was carried out with teachers of the humanities, social and natural sciences from universities in different regions of Russia with at least three years of professional experience. A total of five focus groups of seven teachers in each were conducted.In the context of academic development, digital educational practices were analyzed, and three types of agents were identified – innovators and promoters, who contribute to the academic development of the higher education institutions, and routiners, who slow down the introduction of digital technologies. It is concluded that a possible barrier to the innovative activities for teachers is an ambiguous attitude towards the process of digitalization of the education sector.